Beragam Pendekatan dalam Memahami Hadis Nabi - Prabowo, Yudhi (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2021)
Referring to the hadith and understanding it correctly is a must in the life of humankind today. The dimension of Islamic teachings brought by the Prophet Muhammad saw requires getting correct and accurate information. The text of hadith cannot be separated from the impact of the passage of time. The text of the hadith on its journey from the beginning of the Prophet being sent to become an Apostle, from the first teacher, namely the Prophet, to the bookkeeping of hadith and going through several generations, has experienced an impact in the history of its journey with all its consequences. To understand the hadith correctly, the method of understanding it is felt to be very necessary and necessary to understand the true meaning of a hadith text. All of this cannot be separated from the various sequences that an approach must take to obtain a proportional understanding in the present context as a guide to life in the world and the hereafter need to understand well.ABSTRAKBerpedoman kepada hadis dan memahaminya dengan tepat merupakan suatu keharusan dalam kehidupan umat manusia sekarang. Dimensi ajaran agama Islam yang dibawa Rasulullah SAW mengharuskan mendapat informasi yang benar dan akurat. Karena teks hadis tidak terlepas dari dampak perjalanan waktu. teks hadis dalam perjalanannya dari awal Nabi di utus menjadi Rasul, dari guru pertama yaitu Rasulullah sampai kepada pembukuan hadis dan melewati beberapa generasi, telah mengalami imbas dalam sejarah perjalanannya dengan segenap konsekuensinya. Agar dapat memahami hadis dengan benar maka metode dalam memahaminya dirasa sangat perlu dan keharusan untuk memahami maksud sebenarnya sebuah teks hadis, ini semua tidak terlepas dari runtutan beragam yang harus dilakukan sebuah pendekatan untuk mendapatkan pemahaman yang proporsional dalam konteks kekinian sebagai tuntunan hidup dunia dan akhirat yang perlu dipahami dengan baik.Â  Â Â